Temporal, Spatial, Economic and Crime Factors in Illicit Drug Usage across European Cities - Jacques J.F. Commandeur; Suncica Vujic; Siem Jan Koopman; Barbara Kasprzyk-Hordern (Tinbergen Institute, 2014)
We analyze the illicit drug usage by inhabitants and visitors of European cities. Our statistical analyses are by means of linear mixed models. The data on illicit drug usage of cocaine, ecstasy, amphetamines, methamphetamines, and cannabis are collected through wastewater samples from the inlet of 21 sewage treatment plants spread over 11 European countries. The data set represents nineteen cities, services a population of approximately 15 million inhabitants and covers a one-week period in 2011. The patterns of illicit drug usage are examined with respect to temporal (daily) and spatial variations, as well as in relation to economic wealth (gross domestic product) and criminological (drug offenses recorded by police) factors. In a joint statistical analysis, we find that cocaine and ecstasy are typically recreational drugs that are consumed during the weekend. Inhabitants of Western European countries consume more cocaine than inhabitants of Eastern European countries. This finding cannot be explained by political divisions between West and East. We also find evidence that higher usage of ecstasy is associated with medium-sized cities, economic prosperity, and a lower number of drug offenses.On the other hand, higher usage of methamphetamine is associated with medium-sized cities and low economic wealth.
Keywords: C33; I15; 330; Sewage biomarker analysis; ANOVA; Linear mixed models; Wastewater-based epidemiology